La répression allemande en France, 1940-1944 : principaux chiffres - Louis Poulhès (Cahiers d’histoire.)
This article summarizes the data obtained by the research to date on the German repression during the French Occupation. A table and two graphs present the balance of the two main forms of repression – executions and deportations – implemented by the occupiers between 1941 and 1944, whose evolution appears closely linked to the development of the internal resistance. It is complemented by a focus on German executions at Mont-Valérien and the Balard shooting range in Paris during 1943.